One-Way Fluid-Structure Interaction Study of a Movable Rocket Fin at Various Cant Angles for Aerodynamic Performance and Stability Analysis Under Transient Conditions - Lim, Yau Sheng; Zulkafli, Mohd Fadhli (Progress in Aerospace and Aviation Technology, 2026)
This study investigates the aerodynamic performance and flow behavior of a movable rocket fin at various cant angles under transient conditions using a one-way fluid-structure interaction (FSI) simulation approach. The rocket fin and simplified cylindrical rocket body were modeled in SolidWorks 2025 and imported into ANSYS DesignModeler to create the surrounding fluid domains and computational mesh. Two domains were used: a stationary rectangular outer domain and a rotating cylindrical inner domain around the fin to enable sliding-mesh motion. The meshed domains were then imported into ANSYS Fluent for transient CFD simulation. The cylindrical domain was assigned a constant angular velocity so that the fin rotated from 0° to 15° during the simulation. The results show that increasing the fin cant angle changes the pressure distribution, velocity field, turbulence kinetic energy, aerodynamic forces, aerodynamic moments, and wake structures around the fin. The findings indicate that transient simulation of a prescribed movable fin can aid in understanding how cant-angle variation influences rocket-fin aerodynamic performance and stability.